2009
DOI: 10.1021/ie801467n
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sonochemical Reactor for Physicochemical Transformations

Abstract: Complete knowledge of the pressure field distribution in a sonochemical reactor should be known for an efficient utilization of acoustic energy emitted by the transducers for targeted physicochemical transformations using cavitation phenomena. This work deals with the identification of the active and passive regions in the sonochemical reactor based on the measured pressure field intensities. Iodine liberation experiments based on the decomposition of aqueous potassium iodide (KI) as a representative of cavita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
(51 reference statements)
0
16
0
Order By: Relevance
“…The influence of the drug in various concentrations on the metal loss in MS corrosion has been investigated depending on the limit of its solubility in water at that temperature and the concerned parameters are depicted in Table 1. [5,18] It is clearly seen that the %IE of inhibitor increases and CR decreases with increase in the NSAIDs concentration. Such behaviour could be inferred to the decrease in the weight loss due to the increase in adsorption of inhibitor onto the substrate interface.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…The influence of the drug in various concentrations on the metal loss in MS corrosion has been investigated depending on the limit of its solubility in water at that temperature and the concerned parameters are depicted in Table 1. [5,18] It is clearly seen that the %IE of inhibitor increases and CR decreases with increase in the NSAIDs concentration. Such behaviour could be inferred to the decrease in the weight loss due to the increase in adsorption of inhibitor onto the substrate interface.…”
Section: Resultsmentioning
confidence: 93%
“…[6] In addition to the chemical adsorption, reported studies have shown that the inhibitor molecules do exhibit electrostatic interaction between the charged metal surface and inhibitor. [18] After 4 h of MS immersion in the aggressive acidic environment, it could be seen from Figure 1 that the positively charged NSAIDs molecules get adsorbed on negatively charged MS surface. Thus forming Fe-NSAIDs complexation resulting in a protective layer.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations